Grammar and cognition dualistic models of language structure and language processing - Haselow, Alexander; Kaltenböck, Gunther (Human cognitive processing,, 2020)
"This volume brings together linguistic, psychological and neurological research in a discussion of the Cognitive Dualism Hypothesis, whose central idea is that human cognitive activity in general and linguistic cognition in particular cannot reasonably be reduced to a single, monolithic system of mental processing, but that they have a dualistic organization. Drawing on a wide range of methodological approaches and theoretical frameworks that account for how language users mentally represent, process and produce linguistic discourse, the studies in this volume provide a critical examination of dualistic approaches to language and cognition and their impact on a number of fields. The topics range from formulaic language, the study of reasoning and linguistic discourse, and the lexicon-grammar distinction to studies of specific linguistic expressions and structures such as pragmatic markers and particles, comment adverbs, extra-clausal elements in spoken discourse and the processing of syntactic groups"--